KARAKTERISTIK WARNA L* a* b* DAN TEKSTUR DENDENG DAGING KELINCI YANG DIFERMENTASI DENGAN Lactobacillus plantarum - Anik Fadlilah; Djalal Rosyidi; Agus Susilo (Wahana Peternakan, 2022)
ABSTRACT        This study aims to determine the concentration of L plantarum and the best fermentation time to make fermented rabbit meat dendeng based on L*a*b color and texture of rabbit meat dendeng. The material used was rabbit meat dendeng which was fermented using L. plantarum. The method of research was a experiment of laboratory with a factorial randomized block design and repeated 3 times consisting of concentrations of L. plantarum (0%, 6%, 8%, and 10%) and fermentation time (12, 18 and 24 hours). Based on the analysis of variance, it was found that different concentrations of L. plantarum and fermentation time did not have a significant effect (P>0.05) on the dendeng color of L (brightness), a* (redness) and texture, while the concentration of L. plantarum had a significant effect (P<0.05) and the fermentation time was a significant effect (P<0.05) on the color b* (yellow). The mean of L (Brightness) of dendeng was 33.94-35.72, the mean of a* of rabbit meat dendeng was 13.72-14.63, and b* was 12.53-14.83. The mean of rabbit meat dendeng texture was 22.94-25.25 N. The concentration of L. plantarum and the fermentation time that produced the best characteristic L*a*b* color and texture dendeng was 6% with 18 hours of fermentation time.  Key words: Dendeng; Rabbit; Fermentation; Color; Texture